2021
DOI: 10.1111/ijcp.14974
|View full text |Cite
|
Sign up to set email alerts
|

Effects of garlic extract on lipid profile in patients with coronary artery disease: A systematic review and meta‐analysis of randomised clinical trials

Abstract: This meta‐analysis was conducted to evaluate the effects of garlic extract on total cholesterol (TC), triglycerides (TG), low‐density lipoprotein‐cholesterol (LDL‐c) and high‐density lipoprotein‐cholesterol (HDL‐c), among the patients with coronary artery disease (CAD). Literature searches were conducted in EMBASE, Scopus, PubMed, Web of Science and Cochrane Library until Sep18th, 2020. Inter‐study heterogeneity was examined using Cochrane's Q and I2 tests. The random‐effect models were utilised to pool the we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“…A meta-analysis of randomized controlled trials involving 768 patients with type 2 diabetes mellitus indicated improvement of FPG, plasma fructosamine, glycated hemoglobin, TG, TC, HDL-C, and LDL-C levels following garlic supplementation [40]. However, in another meta-analysis, garlic ameliorated serum TC, but not TG, HDL-C, or LDL-C, in patients with coronary artery disease [41]. Differences in the studied population, study duration, and kind of intervention could potentially explain these conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of randomized controlled trials involving 768 patients with type 2 diabetes mellitus indicated improvement of FPG, plasma fructosamine, glycated hemoglobin, TG, TC, HDL-C, and LDL-C levels following garlic supplementation [40]. However, in another meta-analysis, garlic ameliorated serum TC, but not TG, HDL-C, or LDL-C, in patients with coronary artery disease [41]. Differences in the studied population, study duration, and kind of intervention could potentially explain these conflicting findings.…”
Section: Discussionmentioning
confidence: 99%
“…Garlic-derived polysulfides, particularly S-allylcysteine, also reported to regulate endothelial NO, leading to vasodilation and blood pressure reduction [ 46 ]. Meta-analyses have confirmed the effectiveness of aged garlic extract in lowering blood pressure and improving lipid profiles [ 47 ]. Additionally, various antioxidant compounds have demonstrated antihypertensive effects by targeting distinct pathways, including the modulation of the renin-angiotensin system, vasodilation, and sodium excretion [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Maryam (2021) telah mengemukakan bahwa suplementasi bawang putih dapat menyebabkan penurunan total kolesterol, tetapi tidak mempengaruhi kadar TG, HDL, dan LDL (Kheirmandparizi, 2021). Bawang putih mengandung allicin dan beberapa antioksidan seperti vitamin C, Germanium dan senyawa yang berkaitan dengan sulfur.…”
Section: Pembahasanunclassified